Mixed optical Cherenkov–Bremsstrahlung radiation in vicinity of the Cherenkov cone from relativistic heavy ions: Unusual dependence of the angular distribution width on the radiator thickness; Physics Letters A; Vol. 380, iss. 31-32 - Rozhkova E. I. Elena Ivanovna (2016, 2016)
Title screen